An Empirical Inquiry into Status of Suicidal Ideation among Higher Secondary Students - Gardia, Alok; Shandilya, Shweta (INDIAN EDUCATIONAL REVIEW, 2012)
Suicidal ideation is generally considered as Non-fatal Suicidal Behaviour (NFSB) by most researchers. Across different cultures, the prevalence of NFSB has been found to be alarmingly high among adolescents. As there is no published study estimating prevalence rates in India, a study was conducted on adolescents in Varanasi city to find prevalence of NFSB. Data was collected from 666 higher secondary students through Suicidal Behaviour Questionnaire (SBQ) following descriptive survey method.